(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: Incidence of chronic arterial occlusive disease in lower limbs is high in elder patients. Patients’ s chief complains are intermittent claudication, foot ulcer or even systemic sepsis. Typically, treatment of chronic arterial disease in lower limbs is arterial bypass surgery, endarterectomy. However, these are invasive surgeries, requiring general or spinal anesthesia. Recently, endovascular intervention techniques are applied to the treatment with benefits such as: local anesthesia, fewer complications, and feasible to elder patients with severe compromised disease. Objective: To determine the efficacy of, results of endovascular treatment in patients with symptomatic chronic aortoiliac occlusive disease. Methods: From June 2020 to April 2022, the prospective study was carried out on 56 cases with chronic aortoiliac occlusive disease, treated by PTA in Cardiovascular and Thoracic Department, Thong Nhat hospital. Results: Majority of lesions belong to TASC II C (23%) and D (51%). The artery lesions included simple aortoiliac artery (23%), aortoiliac combined with femoropopliteal and/ or infrapopliteal artery (77%). The ankle- brachial index before and after the intervention is respectively 0.43 ± 0.3 and 0.76 ± 0.29 (p<0.001). Overall, the technical success rate was 96,4%. The complications included internal bleeding (1,8%), limb amputation (7,1%), contrast- induced acute kidney injury (1,8%). The primary patency of revascularization in 1 and 2-year is respectively 97,4% và 76,4%. Conclusion: PTA is a feasible and effective procedure for treatment of lower limb artery disease. However, we need to increase the sample size and more study of long- term patency of PTA should be conducted.